2022
DOI: 10.3390/su14095296
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Environmental Conservation Agriculture (ECA) Utilization among Fujioka Farmers in Japan with High Biodiversity Conservation Awareness but Low ECA Interest

Abstract: Japan aims to be carbon-neutral by 2050 by targeting various sectors including agriculture. One of the main strategies in this sector to mitigate climate change effects is environmental conservation agriculture (ECA); however, ECA utilization remains low in most of Japan’s prefectures to this date. To address this problem and to know what factors influence ECA adoption, we collected data from Fujioka city, Gunma prefecture, which has low ECA utilization but has high biodiversity conservation efforts. Using fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…This could potentially lead to farmers losing confidence in sustainable farming practices and reduce their willingness to adopt ECA. This further highlights the importance of knowledge dissemination among farmers to teach them ECA's climate variability mitigation capabilities, as was also recommended in earlier studies [6,25].…”
Section: Economic Sustainability Of Ecasupporting
confidence: 55%
See 2 more Smart Citations
“…This could potentially lead to farmers losing confidence in sustainable farming practices and reduce their willingness to adopt ECA. This further highlights the importance of knowledge dissemination among farmers to teach them ECA's climate variability mitigation capabilities, as was also recommended in earlier studies [6,25].…”
Section: Economic Sustainability Of Ecasupporting
confidence: 55%
“…Indeed, several studies have already emphasized that farm income can increase farmers' adoption of agricultural technologies [23,24]; therefore, ECA practices should not lead to financial losses or negatively impact farmers' income. For instance, in the study conducted by among ECA farmers in Fujioka, Japan, they reported that making profit is among the top priorities of farmers, aside from making positive contributions to environmental conservation [6]. The paper also emphasized the importance of balancing environmental conservation and profitability to ensure the sustainability of a farming method.…”
Section: Economic Sustainability Of Ecamentioning
confidence: 99%
See 1 more Smart Citation
“…Limiting the use of pesticides or chemical substances will benefit the environment, according to participants with high concerns about biodiversity and ecological resources (Maharjan, Gonzalvo and Aala, 2022a). In another study, Maharjan, Gonzalvo and Aala (2022b) found that ECA has allowed Japanese farmers to earn higher profits by direct selling to consumers.…”
Section: Resultsmentioning
confidence: 99%
“…ECA allows farmers to improve environmental resources and biodiversity (Maharjan, Gonzalvo and Aala, 2022a). In addition, farmers will likely receive higher profits if they incorporate direct selling to consumers (farmers-to-consumers) in their agribusiness (Maharjan, Gonzalvo and Aala, 2022b).…”
Section: Discussionmentioning
confidence: 99%